The Causes of Work Incident According to Work Shift System on Operator of a Woven Bag Company, Sidoarjo - Shintia Yunita Arini (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: In the recent years, woven bag companies have taken a step forward from traditional labor intensive work practices to technological assistance which is operated by workers. Nevertheless, the increased production capability and capacity with assistance of the machineries has been known to cause significant Occupational Safety and Health concerns as having been reported in various previous studies. Therefore, this research aimed to determine the relationship between perception of exposure to hazards and OSH incidents taking into consideration the work shift of the operators. Methods: This research was an analytical observational study with cross-sectional design. There was a total of 67 operators being the population of this study, 53 of whom were recruited as respondents using simple random sampling. The instruments that were used in this research were questionnaires about individual characterization, perception of work environment and work incidents. Variable testing was performed using contingency coefficient. Results: There was a relationship between the complaint towards the noise and the work incident in the morning and afternoon shift. Based on the measurement of the noise, the value was high in the morning of 100dBA, while in the afternoon the value was 91dBA and at night the value was 92 dBA. For the variable of dry temperature, there was a relationship between the complaint towards the dry temperature and the work incident, which showed that in the morning, the dry temperature was 33.1oC. Conclusion: High noise and dry temperature exposure value had a relationship with the work incident on the operators of a Woven Bag Company.Keywords: dry temperature, noise, shift worker, work incident